How Do People Living With HIV Acquire HIV Related Information: A Qualitative Evaluation of Jakarta Setting - Mahathir Mahathir; Wiwin Wiarsih; Henny Permatasari (Jurnal Ners, 2020)
Introduction: People living with HIV are fully aware of their risk behavior and future threats that might arise. The rapid progress of HIV serves the population with many options of healthcare services and treatments. Insufficient knowledge and information will only lower the outcomes of HIV eradication efforts. The ultimate goals to eradicate HIV are to upscale status notification and treat all with appropriate antiretroviral and viral suppression, but it needs sufficient information to administer. Programs and interventions have already been proposed, but an inquiry is needed to ensure all the information is actually there. The study aimed to explore the experience of people living with HIV acquiring HIV-related information.Methods: This study used phenomenological qualitative study and in-depth interviews were conducted to 12 people living with HIV. Semi-structured questions were delivered to all participants which explored their tangible experience in terms of nurturing sufficient HIV-related information.Results: The study found four consequential themes:  non-government organizations play a major role in HIV education, peers are a comfortable platform to discuss, it is all over the media and healthcare personnel are a source of knowledge. Conclusion: The distribution of HIV information and knowledge is now widespread. This situation marks   part of the success in fighting HIV. Remarkable attempts can be maintained by optimizing the viable option of information delivery.  Keyword: HIV knowledge; people living with HIV; qualitative study